Uji Validitas Pengembangan Lembar Kerja Siswa (LKS) Biologi Berbasis Probing Prompting pada Materi Pencemaran Lingkungan MTS Kelas VII untuk Meningkatkan Hasil Belajar Siswa - Siti Qomariyah; Tabitha Sri Hartati Wulandari (Universitas Sebelas Maret, 2018)
The learning process conducted in MTS Al-Musthofawiyah is still conventional and still uses the lecturemethod, thus affecting the students' learning outcomes, which is currently sufficiently high score of 60% withKKM score (70). The currently used Student Worksheet is still simple in terms of materials, drawings andlanguage used, so it needs the development of Student Worksheet (LKS) based on probing prompting onenvironmental pollution material to improve student learning outcomes. The method used is the developmentof ADDIE (Analyze, Desing, Defelopment, Implementation, Evaluation). But in this development only to thestage of Defelopment. The purpose of this research is to know the result of validity test of Student Worksheetwith probing prompting on environmental pollution material to improve student learning result of MTs Al-Musthofawiyah Palang. The instruments used for this study were questionnaires. The result of the validity testfrom the media expert obtained an average value of 82.2%, and the average value obtained from the materialexperts 81% with criteria is very valid, thus it can be concluded that from the test results of the validity of theproduct development of Student Worksheet (LKS) biology-based probing prompting feasible used to improvestudent learning outcomes MTs Al-Musthofawiyah Palang.